2020
DOI: 10.3390/electronics9060900
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-Fuzzy-Based Model Predictive Energy Management for Grid Connected Microgrids

Abstract: With constant population growth and the rise in technology use, the demand for electrical energy has increased significantly. Increasing fossil-fuel-based electricity generation has serious impacts on environment. As a result, interest in renewable resources has risen, as they are environmentally friendly and may prove to be economical in the long run. However, the intermittent character of renewable energy sources is a major disadvantage. It is important to integrate them with the rest of the grid so that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…A blowout, due to mechanical or operational failures that lead to the loss of control of a well, causes a large volume of crude oil to leak directly into the environment, impacting vulnerable factors [4,56] (The EV map for this project is found in [57]). The potential consequences analyzed in this project's EIA only take into account the worst-case blowout scenario.…”
Section: Drillingmentioning
confidence: 99%
See 2 more Smart Citations
“…A blowout, due to mechanical or operational failures that lead to the loss of control of a well, causes a large volume of crude oil to leak directly into the environment, impacting vulnerable factors [4,56] (The EV map for this project is found in [57]). The potential consequences analyzed in this project's EIA only take into account the worst-case blowout scenario.…”
Section: Drillingmentioning
confidence: 99%
“…Comparatively, fossil resources, such as oil and natural gas (NG), are non-renewable, as their formation is on a millennial scale. Unlike solar energy, which is considered "clean", hydrocarbons (HC) damage the planet from the moment of its invasive extraction (that has a risk of spillage) until its use (which releases greenhouse gases (GHG)) [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [15], similarly to [14], the FNNs are optimized to power and voltage regulation and the superiority of FNNs based control systems is shown. In [16], a predictive controller is developed using FNNs for power consumption management and the voltage regulation in daylight irradiation times is studied. In [17], deep discharging problem in PV/battery systems is studied using FNNs and it is shown that by the use of FNNs a better energy balance can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Actual solar radiation and load profile were used in simulation results, which showed the reliability of the system with disturbances such as load variation and PV shading. A similar EMS was proposed based on a neuro-fuzzy inference system [10]. It was compared to a rule-based control strategy to test its reliability.…”
Section: Introductionmentioning
confidence: 99%